Biocompatibility And Toxicity Studies On Heterogeneous Tio2-Zno Polymer Nanocomposite With Enhanced Bacterial Activity - Harun, Nor Hazliana (2022)
Healthcare-associated infections (HAIs) are a major safety concern globally as they contribute to mortality rates amongst patients due to pathogens from direct contact with a contaminated biomedical polymer surface from the indwelling or implanted medical devices. Polymer nanocomposites have become a promising solution for HAIs owing to reactive oxygen species (ROS) and free radicals’ mode of action. In the first section, this work revealed the bacteriostatic and bactericidal potentials of TiO2–ZnO polymer nanocomposite films against HAI pathogens, including multidrug-resistant (MDR) and non-MDR strains. In the second section, the initial analysis of the in vitro bio-interaction responses on fibroblast and blood cell line models showed signs of cell membrane integrity disturbance, which might be due to free radicals’ activities, such as the release of intracellular ROS and Zn ions (Zn2+) during the initial cellular adaptation process on the TiO2–ZnO polymer nanocomposite film. Molecular studies revealed that the cell–polymer nanocomposite film interaction possibly triggered the oxidative stress and pro-inflammatory mechanisms through the principal cascades of Nuclear Factor-κB. Further analysis found that cells could maintain the viability and clonogenic potential and were involved in the anti-apoptosis pathway. Findings suggested the transitory oxidative stress responses of polymer nanocomposite films towards treated cells and not harmful to the cells.